Visual problems in the elderly population and implications for services. Issue 6836 (9th May 1992) - Wormald, R. P.; Wright, L. A.; Courtney, P.; Beaumont, B.; Haines, A. P.
Abstract : OBJECTIVE--To determine the prevalence of visual disability and common eye disease among elderly people in inner London. DESIGN--Cross sectional random sample survey. SETTING--Inner London health centre. SUBJECTS--Random sample of people aged 65 and over taken from practice's computerised age-sex register. MAIN OUTCOME MEASURES--Presenting binocular Snellen 6 m distance acuity and best monocular 3 m Sonksen-Silver acuity to classify prevalence of blindness by World Health Organisation criteria (less than 3/60 in better eye) and American criteria for legal blindness (better eye equal to 6/60 or less) and of low vision by WHO criteria (best acuity 6/18) and visual impairment by American criteria (less than 6/12 or 20/40 but greater than 6/60 or 20/200 in better eye). Principal cause of visual loss by diagnosis, referral indication by cause to hospital eye service, and proportion of cases known to primary care. RESULTS--207 of 288 (72%) eligible people were examined. 17 (8%) housebound subjects were examined at home. The prevalence of blindness was 1% by WHO criteria and 3.9% by American criteria. The prevalence of low vision (WHO criteria) was 7.7%. The prevalence of visual impairment (American criteria) was 10.6%. Cataract accounted for 75% of cases of low vision. Only eight out of 16 patients with low vision were known by their general practitioner to have an eye problem. 56 subjects (27%) would probably have benefited from refraction. Comparisons with studies in the United States and Finland suggested higher rates in this sample, mainly due to the prevalence of disabling cataract. CONCLUSION--There seems to be a considerable amount of undetected ocular disease in elderly people in the community.